8-Cyclopentyl-1,3-dimethylxanthine enhances effectiveness of antidepressant in behavioral tests and modulates redox balance in the cerebral cortex of mice - Mariola Herbet; Aleksandra Szopa; Anna Serefko; Sylwia Wośko; Monika Gawrońska-Grzywacz; Magdalena Izdebska; Iwona Piątkowska-Chmiel; Paulina Betiuk; Ewa Poleszak; Jarosław Dudka (Elsevier, 2018)
The objective of our study was to investigate whether 8-cyclopentyl-1,3-dimethylxanthine (CPT), associated with the adenosine system, enhances the antidepressant efficacy of antidepressant. All experiments were carried out on Albino Swiss mice. Following drugs: CPT (3 mg/kg) and imipramine (15 mg/kg) were administered intraperitoneally (ip), 60 min before tests. Two behavioral tests on antidepressant capability - a forced swim test (FST) and a tail suspension test (TST) - were performed. To examine whether co-administration of CPT with antidepressants affects the redox balance, the lipid peroxidation products (LPO), glutathione (GSH), glutathione disulfide (GSSG), nicotinamide adenine dinucleotide phosphate (NADP+), and reduced nicotinamide adenine dinucleotide phosphate (NADPH) were determined in the cerebral cortex. The results have demonstrated a CPT-induced enhancement of the antidepressant-like effect of imipramine both in the FST and TST, which may indicate that the adenosine system may be involved in the increasing the effect of antidepressant. Co-administration of CPT with imipramine, such as imipramine alone, decreased the NADP+ and LPO concentrations and increased the GSH/GSSG ratio in comparison to the control, which may confirm beneficial - but comparable to imipramine - effect on redox balance under environmental stress conditions. An increase in the concentration of GSSG in the cortex of animals treated with imipramine in ineffective dose compared to control and no such changes after combined administration of both drugs may suggest a favorable oxidation-reduction potential resulting from their synergistic antidepressant effect. Keywords: Depression, CPT, Antidepressant, FST, TST, Oxidative stress